A Business Intelligence Approach to Visualizing and Mapping Families at Risk of Stunting Using Microsoft Power BI: Evidence from Bengkulu - Ahmad Fadhila; Yudi Setiawan; Niska Ramadani (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development and remains a national priority in Indonesia. Bengkulu Province continues to face challenges in managing Families at Risk of Stunting (KRS) data, which are complex and difficult to analyze efficiently using conventional reporting methods. This study aims to design an interactive dashboard for visualizing and mapping Families at Risk of Stunting (KRS) using Microsoft Power BI to support monitoring, evaluation, and evidence-based decision-making at the Bengkulu Provincial BKKBN. The study adopts the Business Intelligence Roadmap, consisting of the justification, planning, business analysis, design, and construction stages. Official secondary KRS data for the 2022–2025 period were preprocessed in Python through data integration, cleaning, validation, and transformation, followed by Exploratory Data Analysis (EDA) to identify data characteristics and regional patterns before dashboard development. The results indicate that the number of families at risk of stunting reached 302,667, with an average risk percentage of 23.39%. Trend analysis revealed a decline in 2024 followed by an increase in 2025, while Bengkulu City, North Bengkulu, and Rejang Lebong consistently recorded relatively higher numbers of families at risk of stunting. The developed dashboard provides interactive visualizations that improve data analysis and support evidence-based decision-making for accelerating stunting reduction in Bengkulu Province.